Growth Pattern of Saccharomyces cerevisiae in Cassava Mill Effluents - Sylvester Chibueze Izah (Journal of Plant and Animal Ecology, 2018)
Nigeria is the world leading producer of cassava. During processing of gari from cassava tuber large volume of effluents are discharged in the environment which is toxic to the environment and some of its associated biota. This study evaluated the growth pattern of Saccharomyces cerevisiae in cassava mill effluents. The Saccharomyces cerevisiae was isolated from palm wine following standard microbiological procedure. The Saccharomyces cerevisiae was inoculated into the sterile effluents and incubated for 15 days. At every 3days interval, 1ml of the effluents was obtained from the medium and the population density determined. Results of the growth showed that the population of Saccharomyces cerevisiae were 0.00 x 106 cfu/ml at day 0 (without inoculum), which rose to 2.88 x 106 cfu/ml at day 3, 272.67 x 106 cfu/ml at day 12 and decline slightly at day 15 (13.57 x 106 cfu/ml). There was significant variations (P<0.05) among the various period of study. The study showed that the growth of Saccharomyces cerevisiae in the effluent was optimum at day 12, then after the density began to decline.
Keywords: Saccharomyces cerevisiae